Dampak Media Sosial Terhadap Pembentukan Karakter Siswa Kelas VII di UPT SMP Negeri 29 Medan - Sitanggang, Ade Tamaria; Siringoringo, Agnes Chintya; Nababan, Cindy; Butar-butar, Ikhsanul Fadly; Saragih, Oktavia Anjelina; Padang, Poliman; Sianipar, Rosaria Ansatasya; Rachman, Fazli (CV. Rayyan Dwi Bharata, 2024)
The rapid development of social media has changed social dynamics, including among students. This research aims to explore the positive and negative impacts of social media on the character formation of class VII students at UPT SMP Negeri 29 Medan. By using a quantitative approach through survey methods, this research reveals that social media has significant potential in enriching knowledge, increasing creativity, and expanding students' social networks. However, on the other hand, unwise use of social media can cause various problems, such as cyberbullying, addiction, and decreased academic performance. These findings emphasize the important role of parents and teachers in assisting students to maximize the benefits of social media while minimizing its negative impacts. Thus, this research provides valuable insight for schools and parents in supporting student character development in the digital era.